Detection and molecular characterization of astro and bocaviruses in dogs in Minnesota. (February 2022) - Sobhy, N.M.; Armién, A.G.; Pilot, J.; Singh, V.; Padhi, S.K.; Muldoon, D.; Goyal, S.M.; Mor, S.K.
Abstract: Canine astrovirus (CAstV) and canine bocavirus (CBoV) are involved in cases of mild, and sometimes severe, gastroenteritis in dogs. Fecal samples from two dead dogs with gastroenteritis were received at the University of Minnesota Veterinary Diagnostic Laboratory to determine the cause of death. Small round viruses of 20–35 nm diameter were observed by negative contrast electron microscopy. The samples were subjected to Illumina MiSeq sequencing. Both samples were strongly positive for CAstV; all viral reads were related to CAstV. In addition, sample number 1 had a few reads of CBoV. Two complete sequences of CAstV were identified (6625 and 6627 nt in length) with 95% nt identity. RT-PCR and PCR were used to confirm CAstV and CBoV infections in successive samples of canine gastroenteritis. Sanger sequencing was done on nucleic acids from positive samples. Of a total of ten samples, CAstV and CBoV infections were confirmed in six and eight animals, respectively. Four animals had mixed infection with both viruses. All sequences of ORF1b gene of CAstVs showed closest clusters in phylogenetic tree with 96–100% nucleotide and amino acids identity. On the other hand, identity between VP2 gene of different CBoV strains in this study ranged from 93%− 100%. All strains were located close to each other except the divergent MT078234 strain, which was arranged in a separate branch and was closer to reference strain JN648103/USA/2010. This study highlights the importance of electron microscopy and next generation sequencing for early detection and characterization of viruses associated with dog gastroenteritis. Highlights: Different strains of CAstVs and CBoVs are circulating in Minnesota, USA, causing fatal gastroenteritis in puppies. Two complete sequences of CAstV were identified with 95% nucleotide identity indicating rapid mutation. All sequences of ORF1b gene of CAstVs showed closest clusters in phylogenetic tree. VP2 gene of different CBoV ranged from 93%− 100% indicating possible existence of variant strains. Electron microscopy and next generation sequencing are important for early detection and characterization of viruses associated with gastroenteritis in dogs.